Response of non-dicamba-resistant soybean varieties to dicamba at varying doses and application times - Meyeres, Tyler Paige (Kansas State University, 2020)
Introduction and rapid adoption of dicamba-resistant (DR) soybeans led to an increase of post-emergent applications of dicamba for weed control during the soybean growing season, resulting in non-target dicamba injury to non-DR soybean. Two separate field studies were conducted in Manhattan, KS in 2018 and 2019 and in Ottawa, KS in 2019 to (1) determine the response of non-DR soybean to reduced rates, different application timings and multiple exposures of dicamba, and (2) investigate the injury and yield response of soybean varieties with varying herbicide-resistant traits when exposed to dicamba. In first study, soybeans were exposed to 0.56 (1/1000X), 1.12 (1/500X), and 5.6 g ae ha⁻¹ (1/100X) rates of dicamba (where 1X rate=560 g ae ha⁻¹) at V3, R1, R3, V3 followed by (fb)R1, V3 fb R3, R1 fb R3, and V3 fb R1 fb R3 growth stages. In second study, four varieties, including ‘Credenz 3841LL (glufosinate-resistant)’, ‘Credenz 4748LL (glufosinate-resistant)’, ‘Asgrow AG4135RR2Y (glyphosate-resistant)’, and ‘Stine 40BA02’ (glyphosate/isoxaflutole-resistant) were exposed to 5.6 g ae ha⁻¹ (1/100X) of dicamba at V3 or R1 growth stages. For both studies, visual soybean injury (%) was evaluated at biweekly intervals throughout the growing season and grain yields were determined at harvest. Injury symptoms, including leaf cupping, brittle leaves, damaged terminal buds, stunting, twisting and pod curling were observed with all dicamba treatments. Soybean injury from dicamba was lower and less persistent when exposed during the V3 than the R1 or R3 growth stages across all dicamba rates tested. Soybean injury symptoms were more severe with increasing dicamba rates and multiple exposures across all site-years. Soybean injury was most severe four weeks after treatment (WAT) and was highest (78% to 81% injury) with the 1/100X rate of dicamba applied at all three timings. Soybean yield reductions were not directly correlated to visual injury and were substantially less than most injury ratings. The highest soybean yield reduction was observed from the 1/100X rate of dicamba applied at V3, R1, and R3, which resulted in a 53% yield loss. Soybean yield loss was minimal from a single dicamba exposure at the V3 stage regardless of exposure rate, or from the 1/1000X rate, regardless of timing or number of exposures. The greatest soybean yield loss from dicamba occurred with multiple exposures at rates greater than 1/1000X rate of dicamba. In the second study, the greatest injury was observed in ‘Asgrow AG4135RR2Y’ and ‘Stine 40BA02’ when exposed to dicamba at V3 growth stage 4 WAT. Dicamba exposure at the R1 growth stage resulted in the greatest injury to ‘Stine 40BA02’ both four WAT and senescence. At senescence, minimal injury was observed in soybean exposed at V3 and also resulted in minimal yield loss. Exposure at R1 resulted in the least yield loss in ‘Credenz 4748LL’ at 19% and the greatest yield loss in Stin 40BA02 at 34%. Dicamba exposure at R1 resulted in the greatest injury and yield loss, while exposure at V3 resulted in minimal injury and yield reduction across all tested soybean varieties.
Keywords: Dicamba; Soybean; injury; Application; timing; Off-target movement